Testing of urodynamic dysfunctions in patients with multiple sclerosis - Babović Rade; Milićević Saša; Radovanović Saša; Jančić Jasna (Vojnosanitetski Pregled)
Background/Aim. Multiple sclerosis (MS) is a chronic autoimmune inflammatory disorder of the unknown origin leading to multifocal demyelization, axonal damage and the loss of the nervous tissue in various parts of the central nervous system. Most MS patients have decreased functionality of the bladder leading to various dysuria disorders during the course of the illness. However, in 2% of the cases dysuric problems are the first symptoms of the disease. Urodynamic testing could help to diagnose functional disorders of the lower urinary tract, which might not be otherwise possible by performing the standard invasive procedures or noninvasive scans, such us ultrasound, computed tomography or functional magnetic resonance imaging (fMRI). Methods. Urodynamic testing - cystometry with electromyographic (EMG) potentials from the external anal sphincter (EAS), was performed in 34 patients (25 female and 9 male patients). Those patients fulfilled Mc Donald’s multiple sclerosis criteria. The urodynamic values were compared to neurological signs and the present disease symptoms. Results. The MS patients with (27) and without (7) miction problems were tested. Detrusor hyperreflexia is the most common finding, present in 58.8% of the cases. More than a half of the patients have detrusor sphincter dissynergia. Conclusions. Urodynamic testing helps us to determine neurological disorders characteristics and to prepare an appropriate treatment plan. During the course of the disease different urodynamic disfunctions may occur as well as changes in the urinating functionality. The rationale for urodynamic testing in patients suffering from MS before any other treatment procedure is to confirm the diagnosis of dysuric disorders and to secure appropriate treatment.